Анализ демпфирующих свойств различных материалов под установку миномета калибра 120 мм на шасси бронетранспортера - Токарь, С. Е.; Каторгин, А. Н.; Дудко, В. В.; Сергиенко, А. А.; Павлов, А. Е. (НТУ "ХПИ", 2014)
У статті наведені результати досліджень різних матеріалів, що дозволяють зменшити динамічні навантаження самохідної установки при стрільбі з міномету калібром 120 мм, встановленому на шасі бронетранспортера БТР-3Е.

The article describes the results of studying various materials that make it possible to decrease dynamic loads of the self-propelled system when firing 120 mm mortar installed on the BTR-3E armoured personnel carrier.
Analysis of the damping properties of various materials used for installing a 120 mm mortar on the armoured personnel carrier
Keywords: боевые бронированные машины; бронетехника; бронетанковая техника; артиллерийское орудие; миномет; минометные установки